2019
DOI: 10.1136/bcr-2019-230402
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular acidosis as the initial presentation of Sjögren’s syndrome

Abstract: We present a 44-year-old female with an initial presentation with distal renal tubular acidosis (RTA) after she presented with hypokalaemia and normal anion gap acidosis. Three years following the diagnosis, she presented with progressive renal impairment. In the absence of any clinical, biochemical and radiological clues, she underwent a renal biopsy which showed severe tubulitis secondary to lymphocytic infiltration. Serological investigations subsequently revealed positive anti-nuclear, anti-Sjögren’s syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Jha et al 35 and Pisanty and Markitzio 36 reported a history of similar disease in an identical twin sister and paternal aunt of their index patients, respectively. Ho et al 37 reported a history of hypokalemia requiring supplementation in the aunt and cousin of the index patient. Family history of systemic autoimmune diseases reported in the first‐degree relatives of index patients included lupus in two, and one each of SS, lupus/scleroderma overlap and discoid lupus, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Jha et al 35 and Pisanty and Markitzio 36 reported a history of similar disease in an identical twin sister and paternal aunt of their index patients, respectively. Ho et al 37 reported a history of hypokalemia requiring supplementation in the aunt and cousin of the index patient. Family history of systemic autoimmune diseases reported in the first‐degree relatives of index patients included lupus in two, and one each of SS, lupus/scleroderma overlap and discoid lupus, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrent parotid swelling has been documented as the most common presenting feature in the pediatric population, occurring more frequently than sicca symptoms [8]. The most common renal manifestation of Sjögren's syndrome is tubulointerstitial nephritis, which may present as RTA in adult populations; however, RTA is a rare occurrence in the pediatric population as it accounts for 7.1-19.2% of cases who present with renal potassium wasting or hypokalemic paralysis [9]. Our patient first presented with an episode of muscle weakness and syncope in the setting of severe hypokalemia at the age of 14 years, often exacerbated by menses.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional case reports with this association were published in 2020, and another study published recently showed a prevalence of 14.81% of DRTA (16 patients) in a cohort of 108 patients with SLE [ 6 , 7 , 8 ]. Generally, the majority of cases with complete DRTA published in literature are diagnosed due to severe symptoms associated with hypokalemia, such as quadriparesis or even respiratory arrest, and therefore, the real prevalence of DRTA associated with autoimmune diseases is difficult to estimate [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, urinary acidification tests are essential in diagnosing those patients who did not develop any symptoms and would otherwise escape undiagnosed.…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Aiming for a better understanding of the disease, we performed a search of the PubMed database using MeSH descriptors (Acidosis, Renal Tubular; Lupus Erythematosus, Systemic; Sjogren’s Syndrome, Systemic Vasculitis, Rheumatoid Vasculitis, Arthritis, Rheumatoid, Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis, Churg-Strauss Syndrome, IgA Vasculitis, Spondylitis, Ankylosing, Cryoglobulins, Hepatitis, Autoimmune, Liver Cirrhosis, Biliary), and we identified 37 individual case reports published since December 2016 with the association of distal renal tubular acidosis and the following autoimmune disorders: SLE, Sjögren’s syndrome, autoimmune hepatitis, primary biliary cirrhosis and rheumatoid arthritis (see Table 1 ) [ 6 , 10 , 11 , 13 , 15 , 16 , 17 , 18 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. We also identified a case of hereditary autoimmune polyendocrine syndrome (DRTA, hypoparathyroidism, Addison disease), published in a series of cases, which was not included in our analysis, due to the lack of individual data availability [ 39 ].…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation